Analisis Pengaruh Faktor-Faktor Ekuitas Merek Terhadap Keputusan Pembelian Produk Sepeda Motor Yamaha Mio-J di Kota Tomohon - Runtuwene, Indra K (JURNAL RISET BISNIS DAN MANAJEMEN)
This study uses associative research. A data analysis technique was using multiple linear regressions. Results showed simultaneously or jointly variable Brand Awareness, Brand Association, Perceived Quality and Brand Loyalty have an influence on product purchasing decisions Motorcycles Yamaha Mio - J. In partial, Brand Awareness, Brand Association, Perceived Quality and Brand Loyalty significantly influence the buying decision Products Motorcycles Yamaha Mio - J and Brand Awareness variable most dominant influence on purchasing decisions. Brand Equity as a whole is strong but given the competition with other products which are so tight as new and old players who continue to innovative and dynamic then the company should be more aggressively and continuously improve the services and continue to strengthen the brand image by implementing marketing promotion to increase consumer brand awareness.Keywords: equity, awareness, association, brand